On the Solution of Stochastic Generalized Burgers Equation - Dib, Nidal; Guesmia, Amar; Daili, Noureddine (Communications in Mathematics and Applications, 2018)
We are interested in one dimensional nonlinear stochastic partial differential equation: the generalized Burgers equation with homogeneous Dirichlet boundary conditions, perturbed by additive space-time white noise. We propose a result of existence and uniqueness of the local solution to the viscous equation using fixed point argument, then if we impose a condition to the viscosity coefficient we can prove that this solution is global.